2014
DOI: 10.1371/journal.pone.0084598
|View full text |Cite
|
Sign up to set email alerts
|

Deriving a Mutation Index of Carcinogenicity Using Protein Structure and Protein Interfaces

Abstract: With the advent of Next Generation Sequencing the identification of mutations in the genomes of healthy and diseased tissues has become commonplace. While much progress has been made to elucidate the aetiology of disease processes in cancer, the contributions to disease that many individual mutations make remain to be characterised and their downstream consequences on cancer phenotypes remain to be understood. Missense mutations commonly occur in cancers and their consequences remain challenging to predict. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…There are various methods which predict the phenotypic effects of mutations, (3033, 41) and some of them use structural features (31, 41). We applied four state-of-the-art independent methods to predict the impacts of mutations on CBL function: PROVEAN (30), PolyPhen-2 (31), MutationAssessor (32) and InCa (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various methods which predict the phenotypic effects of mutations, (3033, 41) and some of them use structural features (31, 41). We applied four state-of-the-art independent methods to predict the impacts of mutations on CBL function: PROVEAN (30), PolyPhen-2 (31), MutationAssessor (32) and InCa (33).…”
Section: Resultsmentioning
confidence: 99%
“…We also applied four additional webtools to assess the impacts of amino acid substitutions on CBL function: PROVEAN (30), PolyPhen-2 (31), MutationAssessor (32) and InCa (33). (See Supplementary Methods for more information.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, MSEA-domain is hypothesis-driven and provides a better interpretation of the resultant genes, since most domains are known for their functions. For example, MSEA-domain can be extended for scenarios where regions are defined using biological functional units, such as protein pockets [46], protein secondary structure units [47,48], or regulatory regions (for example, promoters, untranslated regions). In practice, we suggest the user apply both methods and combine the results, in order to find all possible mutation hotspots.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that disease-causing mutations commonly alter protein folding, protein stability, and proteinprotein interactions (PPIs), often leading to new disease phenotypes [8][9][10][11][12][13][14][15][16][17][18][19][20]. Espinosa et al [21] proposed a predictor, InCa (Index of Carcinogenicity) that integrates somatic mutation profiles from the Catalogue of Somatic Mutations in Cancer (COSMIC) database and the neutral mutations from the 1000 Genomes project into protein structure and interaction interface information. Using these data, they developed the InCa classifier model to predict cancer-related mutations with 83% specificity and 77% sensitivity.…”
Section: Introductionmentioning
confidence: 99%